Electro-hydrodynamic convection in a rotating dielectric micropolar fluid layer - Kaur, H.; Verma, G.N. (Zielona Góra: Uniwersytet Zielonogórski)
Thermal convection of a rotating dielectric micropolar fluid layer under the action of an electric field and temperature gradient has been investigated. The dispersion relation has been derived using normal mode analysis. The effects of the electric Rayleigh number, micropolar viscosity, Taylor number and Prandtl number on stability and over stability criteria are discussed. It is found that rotation postpones the instability in the fluid layer, while the Prandtl number and rotation both have a stabilizing effect. It is also observed that the micropolar fluid additives have a stabilizing effect, whereas the electric field has a destabilizing effect on the onset of convection stability.
Keywords: convection; rotation; electric; Rayleigh number; Taylor number; normal-mode